Scheme to Increase Sex Ratio in Haryana - priti (Innovative Research Thoughts, 2017)
In Haryana, there are many evidences that point out female birth is as burden on family. In Haryana result shows rapidly lowest child sex ratio report by the 2001&2011 census. Haryana is amongst the most affected state regarding declining and imbalance of child sex ratio. Therefore, this state is the main focus area of this study. Though there are the many reasons behind decline in the child sex ratio, but the most significant is the son preferences in Haryana. This study has given some suggestions for the upgrading of the socio-cultural and socio-economic fundamental and increase the value of daughters to their parents in this modern era. Using data from the Census of India and the National Family Health Survey, this paper shows challenges, causes, trends and declining in child sex ratios in Haryana. Latest census data (2011) shows that the child sex ratios have decreased compared to data from the last years. Increasing son preference and ignore of daughters in many district in Haryana. The main objective of this research is to evaluate imbalance in child sex ratio challenges and emerging issues in Haryana. This study provides result that people of Haryana always preferred birth of son as compared to the daughter. This paper also shows that the South Indian states have higher child sex ratio as compared to Haryana.